Characterization of phosphorus compounds in soils by deep ultraviolet (DUV) Raman microspectroscopy. (10th February 2017) - Vogel, Christian; Ramsteiner, Manfred; Sekine, Ryo; Doolette, Ashlea; Adam, Christian
Abstract : Deep ultraviolet Raman microspectroscopy was successfully investigated as a new approach to analyze the chemical state of phosphorus compounds directly in soil. We demonstrate that ultraviolet excitation has the advantage to avoid the interference with the strong fluorescence, which occurs in the visible spectral range caused by organic matter in soils. Furthermore, the spatial resolution of <1 μm 2 enables the detection of very small phosphorus particles. For some organic phosphorus compounds (β‐glycerophosphate, aminomethylphosphonic acid), sample cooling to −100 °C is found to strongly reduce the rate of degradation induced by the illumination with the ultraviolet excitation light. However, phytic acid and adenosine monophosphate degraded even with cooling. Our results reveal the capability of deep ultraviolet Raman microspectroscopy as a high‐resolution benchtop imaging technique for the analysis of local interactions between soil compounds with the potential to become an analytical key to improve the understanding of transformation mechanisms of phosphates as well as other mineral phases in soils. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Deep ultraviolet Raman microspectroscopy was successfully investigated as a new approach to analyze the chemical state of phosphorus compounds directly in soil. We demonstrate that ultraviolet excitation has the advantage to avoid the interference with the strong fluorescence, which occurs in the visible spectral range caused by organic matter in soils. For some organic phosphorus compounds, intensive sample cooling is found to strongly reduce the rate of degradation induced by the illumination with the ultraviolet excitation light.